Feasibility and effects of mindfulness-based stress reduction (MBSR) for improving resilience, posttraumatic stress disorder symptoms and posttraumatic growth among military medical college students - Xiaofan Yan; Xiaojie Wang; Yanli Chen; Xiaoxiao Xu; Li Peng; Yuanyuan Xu (Acta Psychologica)
Background: Increased stress among medical students in military college has been a challenge in the field of education. One approach to addressing stress reduction is mindfulness training. MBSR has been verified to improve the health status of different individuals. The aim of this study was to examine whether MBSR improves the psychological resilience, posttraumatic stress and posttraumatic growth of medical students in military college. Methods: MBSR was performed with students from a military medical university. A total of 372 students were surveyed by questionnaires, including the 10-item of Connor-Davidson Resilience Scale, Posttraumatic Growth Inventory, PTSD Checklist for DSM-5, Satisfaction with Life Scale, and Mindful Attention Awareness Scale, before the intervention, after the intervention and one month later. A control group of students also answered the questionnaires at the three time points but did not participate in the MBSR intervention. Statistical analyses were performed using repeated-measures ANOVA. Results: The results suggest that the MBSR group experienced significant improvements in resilience, posttraumatic growth, life satisfaction, and mindful attention awareness scores, as well as significant reductions in depression, anxiety, and PTSD intrusive symptoms scores after the intervention. These results were not found in the control group. One month after the intervention, all of these variables showed varying degrees of maintenance effects in the MBSR group. Conclusion: The MBSR intervention was effective, as the medical students in military college in the MBSR group exhibited improvements in psychological resilience, posttraumatic growth, satisfaction with life and mindful attention awareness, depression, anxiety and intrusive symptoms.